Fainting of social activity as the leading constituent of modem pedagogics (Pedagogy of Higher and Secondary Education, 2006)
In the article the problem of scientific approach is examined to organisation to the process of education of social activity of young people. On the basis analysis of researches in area of philosophy, sociology, psychophisiologe, history,. pedagogics the complex model of social activity is offered as factor of trunsinon of society on the new level of development.
Keywords: society; information society; social activity; becoming frequent youth